Incidence of congenital hypothyroidism in special region of Yogyakarta in 2018-2020 - Sabella Rahmawati, Rhea; Ratnaningsih, Tri; Windarwati, Windarwati; Yudha Patria, Suryono (International Journal of Public Health Science (IJPHS), 2024)
Congenital hypothyroidism (CH) is an inadequate thyroid hormone in newborns and is one of the most common causes of preventable mental retardation. It is crucial to do CH screening in newborns aged a few days to detect early occurrences of CH so that intervention can be done immediately. Screening for CH was introduced in Indonesia in 2000, and by 2014, the percentage of newborns screened remained less than 1% of the total. The Special Region of Yogyakarta, one of Indonesia's provinces, has not been the subject of any research regarding the incidence of CH. Hence, this study aimed to investigate the incidence of CH in the Special Region of Yogyakarta during the period from 2018 to 2020. This study, conducted from January 2018 to December 2020, investigated CH incidence in Yogyakarta using data from 23,787 screened newborns. Nine were diagnosed with primary CH. Incidence of CH in this study was higher in males than females, small for gestational age (SGA) than appropriate for gestational age (AGA), and preterm than term, with no significant differences between the variables and CH incidence. Therefore, the incidence in the Special Region of Yogyakarta in 2018-2020 was found to be 1:2,643.